Pengaruh Penempatan Kerja, Kompensasi dan Lingkungan Kerja Terhadap Kinerja Pegawai Koordinator Statistik Kecamatan Badan Pusat Statistik Kabupaten Ciamis - Joni Kurniawan; Aini Kusniawati; Ferey Herman (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
An organization is established because it has a goal that it wants and must achieve. A government organization is established with the aim of providing civil and economic rights services to every citizen optimally. A company organization is established by a group of people because they want to gain business profits, while a non-profit organization is established with the aim of community service. The purpose of this study is to determine and describe the influence of job placement on the performance of employees of the Sub-district Statistics Coordinator of the Central Statistics Agency of Ciamis Regency. The influence of compensation on the performance of employees of the Sub-district Statistics Coordinator of the Central Statistics Agency of Ciamis Regency. The influence of the work environment on the performance of employees of the Sub-district Statistics Coordinator of the Central Statistics Agency of Ciamis Regency. The influence of job placement, compensation, and work environment on the performance of employees of the Sub-district Statistics Coordinator of the Central Statistics Agency of Ciamis Regency. The method used in this study is descriptive and verification research. Based on the results of the research and discussion, the following conclusions are obtained. Job placement tends to increase and employee performance tends to increase. Thus, job placement affects employee performance at the Central Statistics Agency of Ciamis Regency. Compensation tends to increase and employee performance tends to increase. Thus, compensation affects employee performance at the Central Statistics Agency of Ciamis Regency. The work environment tends to increase and employee performance tends to increase. Thus, the work environment affects employee performance at the Central Statistics Agency of Ciamis Regency. Job placement tends to increase, compensation tends to increase and the work environment tends to increase and employee performance tends to increase. Thus, job placement, compensation and work environment affect employee performance at the Central Statistics Agency of Ciamis Regency